Adaptive Coded Modulation for OFDM System (Journal of Engineering, 2012)
This paper studies the adaptive coded modulation for coded OFDM system using punctured convolutional code, channel estimation, equalization and SNR estimation. The channel estimation based on block type pilot arrangement is performed by sending pilots at every sub carrier and using this estimation for a specific number of following symbols. Signal to noise ratio is estimated at receiver and then transmitted to the transmitter through feedback channel ,the transmitter according to the estimated SNR select appropriate modulation scheme and coding rate which maintain constant bit error ratelower than the requested BER. Simulation results show that better performance is confirmed for target bit error rate (BER) of (10-3) as compared to conventional modulation schemes, the convolutional coded modulation offers a SNR gains of 5 dB compared to uncoded state at BER of 10-3. The proposed adaptive OFDM scheme maintains fixed BER under changing channel conditions.